Local Economic Transformation through International Collaboration: Optimizing the Creative Economic Potential of Edelweiss Flowers Based on Sharia Principles - Ismawati; Hastin Tri Utami; Andi Bahri S; Inarotul A'yun; Dewi Maharani; Mitra Sami Gultom; Atina Hidayati; Nuur Halimatus Saadiah Masrukhin; Hanim Misbah; Puspita; Alip Toto Handoko (Yayasan Darussalam Patalassang, 2025)
This Community Service Program (PKM) aims to support local economic transformation among the Tengger Tribe by optimizing creative economic potential based on the edelweiss flower through a sharia-based framework and international collaboration between Indonesian universities that are members of APSKPS and Malaysian universities. A participatory approach was applied through observation, interviews, focus group discussions, documentation, and direct educational mentoring for local micro‐entrepreneurs. The findings reveal improved Islamic financial literacy, enhanced portable digital marketing capacity, and strengthened ecological awareness regarding the conservation of edelweiss as a culturally valuable yet environmentally sensitive species. Collaboration with USIM, UiTM, and UKM enabled cross-country knowledge transfer that enriched empowerment strategies and broadened the community’s orientation toward sustainable creative economy development. This program integrates Islamic spiritual-ecological values, environmental preservation, and digital innovation into a single framework rooted in maqashid shariah. The results indicate that economic utilization of edelweiss does not require harvesting from natural habitats, but can be developed through non-destructive derivative products and creative digital content grounded in local culture. This model serves as an example of inclusive, sustainable, and socially just community empowerment.